Shape Casting 7th International Symposium Celebrating Prof. John Campbell's 80th Birthday - Tiryakioğlu, Murat; Griffiths, William; Jolly, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book contains a collection of papers on the science, engineering, and technology of shape casting, with contributions from researchers worldwide. Among the topics that are addressed are the structure-property-performance relationships, modeling of casting processes, and the effect of casting defects on the mechanical properties of cast alloys.
Part 1. Entrainment and Bifilms -- Update on Bifilms -- The Fundamental Defect in Metals -- Entrainment Defects in Cast Iron -- Measurement of Air Entrainment During Pouring of an Aluminum Alloy.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering